Samin Foundation Therapeutic Communication Process to Children Victims of Violence to Return Children’s Public Space in Sleman District DIY Year 2018-2019 - Suciati, Suciati; Aulia, Erlie (Universitas Muhammadiyah Yogyakarta, 2021)
This study examines the therapeutic communication method carried out by the SAMIN Foundation in Sleman Regency, Yogyakarta Special Region (DIY). According to the head of the KPAI, cases of violence against children in Indonesia are caused by the weak knowledge of the community and parents about the meaning of child protection. DIY is a province that ranks 4th at the national level for cases of violence against children. DIY is a child-friendly area program that is a sustainability program and is related to other programs so that the programs initiated by the DIY Children's Forum are more numerous than Papua, DKI Jakarta, and Central Java. The Sleman Regency Government is aware of the importance of protection rights to be given to children. This is evidenced by the existence of a more systematic program to empower and protect children, and several awards that have been won. The purpose of this study is to describe the therapeutic communication process by the SAMIN Foundation to children who are victims of violence to restore children's public spaces in Sleman DIY. This research uses descriptive qualitative. The data collection process was carried out by interviewing and observing two therapist informants, two-child informants, and government agencies in collaboration with the SAMIN Foundation. The results showed that the stages in conducting therapeutic communication were the pre-interaction phase, the interaction phase, the work phase, and the termination phase. In the pre-interaction phase, the therapist also analyzes the problems experienced by the child. The method used is data mining by assessment or mapping, through direct question and answer, drawing method, Thematic Apperception Test (TAT), and Children Apperception Test (CAT). While the methods used are the drawing method, the writing method, the therapy with songs, the therapy with the film, and the playing method.